Manajemen Kepala Sekolah sebagai Upaya Peningkatan Profesionalisme Guru - Moh. Zahiq (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
The world of education from time to time began to experience rapid development, therefore, to manage and develop education in schools requires management knowledge and a leader/head, therefore the principal is in charge of improving the education system so that education is more efficient and effective. And the principal serves as a supervisor, as a manager, as an educator, and as an entrepreneurship developer, in carrying out his duties the principal needs teaching staff who have different logic, personality, social, and professional potential. Professional teachers have personal, social, intellectual, moral, and spiritual responsibilities, and can carry out their duties as teachers. Professional teachers have adequate professional education qualifications, have abilities following their fields. because management science is one of the most important aspects in managing an institution or agency, including educational institutions.